Improving Emergency Call Accessibility via Location Technologies in Romania - Bokor, Edita; Botiș, Horia Răzvan; Sava Crețescu, Alina; Nen, Madlena; Certan, Corina Daniela (International Journal of Engineering and Management Sciences, 2025)
This study examines Romania’s progress in emergency caller location technologies and accessibility between 2020 and 2024, within the broader European context. Applying a PRISMA-informed review methodology, it draws on official reports, academic sources, and EU regulatory data to evaluate the implementation of Advanced Mobile Location (AML), HTML5 geolocation, and the Apel 112 mobile application Romania was among the first EU countries to deploy AML and subsequent performance metrics indicate notable advancements in geolocation accuracy through hybrid handset- and network-based methods. However, despite these advancements, the adoption of the Apel 112 app has declined, raising concerns about user trust, public awareness, and accessibility. To assess system inclusiveness, this study applies the International Classification of Functioning, Disability and Health (ICF) framework. Findings reveal that persons with hearing, speech, and cognitive impairments continue to face substantial barriers due to the absence of real-time text (RTT), video relay services, and universally designed interfaces. These results support both hypotheses: Romania has strengthened its technical infrastructure for caller location (H1), yet persistent accessibility and interoperability limitations remain (H2). The study concludes that inclusive design, user education, and cross-platform compatibility must become priorities for emergency communication policy to ensure equitable access for all users.